Kate the great : winner takes all - Becker, Suzy (Becker, Suzy. Kate the great, 2016)
"Armed with her smarts, an artillery of doodles, and maybe even some advice from Eleanor Roosevelt, Kate must find a way to keep her friends, old and new"--